ANALYSIS OF TEMPORAL VARIABILITY OF TIDEs AT STASIUN PASANG SURUT MAUMERE ON JANUARY 2023 - Saumarachmawati, Putri Ani; Pramudya, Yudhiakto (EduFisika: Jurnal Pendidikan Fisika, 2025)
Tides is caused by the gravitational forces of celestial bodies such as the sun and moon, lead to fluctuations in sea level on Earth. This study analyzes the frequency and height of tides measured by the Maumere tidal station (Stasiun pasang Surut Maumere) from January 12 to 14, 2023, comparing observed changes with theoretical predictions. The Fast Fourier Transformation (FFT) method, implemented via Microsoft Excel, was employed to dissect the tidal signal into its frequency components. Results indicate that the Maumere sea exhibits a diurnal tide cycle with an average height of 1.57 m during the observation period. The observed maximum tidal height change was 0.76 m, while the theoretical prediction, based on the Earth-moon distance of 0.37 million km on January 14, was 0.6 m. The root mean square error (RMSE) between observed and predicted tidal heights was 0.34 cm. This analysis demonstrates that FFT can effectively characterize tidal frequencies and contributes to the understanding of tidal behaviors, enhancing predictive models in oceanography.